Hydrodynamic forces on a submerged horizontal circular cylinder in uniform finite depth ice covered water - Sahu, M.; Das, Dilip (Zielona Góra: Uniwersytet Zielonogórski)
Hydrodynamic forces on a submerged cylinder in uniform ?nite depth ice-covered water is formulated by using the method of multipoles, the ice-cover being modelled as an elastic plate of very small thickness. The forces (vertical and horizontal) are obtained analytically as well as numerically and depicted graphically for various values of ?exural rigidity of the ice-cover to show the effect of its presence. When the ?exural rigidity and surface density of the ice-cover are taken to be zero, then the curves for the forces almost coincide with the curves for the case of uniform ?nite depth water with free surface.
Keywords: wave scattering; hydrodynamic forces; submerged cylinder; ice-covered water